Efficacy of ultrasonics and Er,Cr:YSGG laser on root surface calculus removal: A comparative in vitro field emission scanning electron microscope study - Afreen Jannath; Rajasekar Sundaram; Suganya Selvarangam; Krishnan Viswanathan; Srinivasan Sivapragasam (Journal of Advanced Periodontology and Implant Dentistry)
Background. Scaling and root planing (SRP) is an inevitable primary step in non-surgical periodontal therapy. Debridement carried out with manual instruments and ultrasonics results in the removal of tooth structure. Current research revolves around laser as an efficient adjunct to SRP. This study evaluated and compared the effectiveness of root surface calculus removal between ultrasonics and Er,Cr:YSGG laser. Methods. Twenty-eight single-rooted teeth extracted due to periodontal disease were selected for the study. The specimens were randomly assigned to two groups (n=14). Group I underwent ultrasonic instrumentation using a piezo ultrasonic scaler, and group II was subjected to laser instrumentation using Er,Cr:YSGG laser (Waterlase). The specimens were processed, fixed, viewed under a field emission scanning electron microscope and evaluated using the remaining calculus index (RCI) and loss of tooth substance index (LTSI). Results. Ultrasonics-treated specimens revealed more remaining calculus (1.57±0.65) and lost tooth substance (1.71±0.61) compared to the Er,Cr:YSGG laser-treated specimens, with significantly lower RCI (0.71±0.61) and LTSI (1.00±0.56). There was a statistically significant difference (P<0.05) in the efficacy of root surface calculus removal between the two groups. Conclusion. Compared to ultrasonics, Er,Cr:YSGG laser demonstrated superior results by causing precise removal of root surface calculus without significantly affecting tooth structure and aiding in new attachment.